Application of modern communication technology in the specialized hospital for prevention and control of COVID-19 (现代通讯技术在新型冠状病毒肺炎专科医院中的应用) - JING Tiaoping (景调平); JIN Ping (金萍); LI Tianfeng (李田峰); JIN Yuntao (金蕴韬) (中西医结合护理)
The management of specialized hospital for prevention and control of COVID-19 does appear to be on the cusp of a new phase, and efficient transmission of information is an important precondition for clinical practice. This paper summarized the application of modern communication technology in the specialized hospital for prevention and control of COVID-19. Involvement of modern means of communication has been improving the hospital information service system, and will play a great role in socialized management and control of infection, as well as clinical practice. (新型冠状病毒肺炎专科医院的管理和运行模式均处于全新的阶段, 信息的有效传递时保证临床工作有序开展的重要前提。本文总结了现代通讯技术在新型冠状病毒肺炎专科医院中的应用现状。现代通讯手段的介入使得医院的信息服务体系更趋于完善, 且在未来传染病的社会化管理和临床工作中将会发挥更大的作用。)